2021
DOI: 10.1039/d1ra03417k
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive antimicrobial coating based on a PEDOT-fullerene C60 polymeric dyad

Abstract: A photostable and photodynamic antimicrobial surface was developed. The antimicrobial activity of the material reached outstanding levels of inactivation under different conditions: planktonic suspensions, adhered cells to the surface, and biofilms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 84 publications
2
22
0
Order By: Relevance
“…Also, two small peaks, located at 437 and 705 nm, can be observed for P‐C 60 . These ones are distinctive and diagnostic of N ‐methylfulleropyrrolidines [17,47] . Furthermore, P‐C 60 has high absorption in the UV‐region corresponding to π‐π* transitions of the fullerene moiety [17,37] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, two small peaks, located at 437 and 705 nm, can be observed for P‐C 60 . These ones are distinctive and diagnostic of N ‐methylfulleropyrrolidines [17,47] . Furthermore, P‐C 60 has high absorption in the UV‐region corresponding to π‐π* transitions of the fullerene moiety [17,37] …”
Section: Resultsmentioning
confidence: 99%
“…These ones are distinctive and diagnostic of N-methylfulleropyrrolidines. [17,47] Furthermore, P-C 60 has high absorption in the UV-region corresponding to π-π* transitions of the fullerene moiety. [17,37] Regarding the dyad BP-C 60 , it is easily observed that the absorption spectrum of BP-C 60 corresponds to a linear combination of the two constitutional components BP and P-C 60 .…”
Section: Absorption and Fluorescence Spectroscopic Characterizationmentioning
confidence: 99%
“…It was observed that the inactivation was accomplished after 30 min of irradiation using the same light dose as reported here for ZnPc-PEDOT (3.6 J/cm 2 ). 18 Until now, the improvement of self-sterilizing surfaces by the addition of KI in PDI treatments was never reported. Our results provide evidence on how a relatively weak antimicrobial material can be significantly improved by simply aerosolizing a low-cost inorganic salt on the material.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The generation of photoactive polymers by electrochemical procedures is a reliable way to obtain antimicrobial surfaces. Exploiting electrochemical procedures it is possible to generate polymeric films controlling their morphology and thickness. To this end, tetrapyrrolic derivatives bearing amino, diethyl aniline, and thiophene , have been synthesized. However, there are only a few reports about the use of ethylenedioxythiophene (EDOT), a monomer that polymerizes to form polyethylenedioxythiophene (PEDOT), one of the most versatile and conductive materials .…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial properties are also found in carbon nanomaterials, which include graphene, carbon nanotubes, fullerenes, and various forms of diamonds [4][5][6][7][8][9][10]. Moreover, it was shown that the antibacterial properties of C 60 fullerenes are not associated with the production of reactive oxygen species (ROS), and materials based on them exert oxidative stress independent of ROS [11][12][13][14], thereby significantly reducing cytotoxicity. The ability of fullerene to photocatalyze in a nanocomposite can be used to create self-cleaning materials [15].…”
Section: Introductionmentioning
confidence: 99%